Performance Improvement Based Authentication Protocol for Intervessel Traffic Service Data Exchange Format Protocol Based on U-Navigation System in WoT Environment. (7th August 2014) - Lee, Byunggil; Park, Namje
Abstract : International Association of Lighthouse Authorities (IALA) is developing the standard intersystem VTS exchange format (IVEF) protocol for exchange of navigation and vessel information between VTS systems and between VTS and vessels. VTS (vessel traffic system) is an important marine traffic monitoring system which is designed to improve the safety and efficiency of navigation and the protection of the marine environment. And the demand of Inter-VTS networking has been increased for realization of e-Navigation as shore side collaboration for maritime safety. And IVEF (inter-VTS data exchange format) for inter-VTS network has become a hot research topic of VTS system. Currently, the IVEF developed by the International Association of Lighthouse Authorities (IALA) does not include any highly trusted certification technology for the connectors. The output of standardization is distributed as the IALA recommendation V-145, and the protocol is implemented with an open source. The IVEF open source, however, is the code used to check the functions of standard protocols. It is too slow to be used in the field and requires a large memory. And the vessel traffic information requires high security since it is highly protected by the countries. Therefore, this paper suggests the authentication protocol to increase the security of the VTS systems using the main certification server and IVEF.